Froth flotation of lithium micas – A review - Korbel, C.; Filippova, I.V.; Filippov, L.O. (Minerals engineering, 2023)
Flotation of lithium micas and especially lepidolite is becoming a matter of increasing interest, as a result of the increased demand in lithium for the battery and other sectors of modern technology. Gangue minerals of lithium-mica deposits behave similarly during flotation, resulting in a difficult separation contrast. The aim of this article is to review available data on crystallography and surface properties of Li-bearing micas in relation to physical–chemical properties such as electrokinetic potential and flotation behaviour, and reagents used to recover lepidolite (i.e., collectors, modifiers, promoters, depressants, etc.). Collectors used, either alone or in mixture, for their flotation are screened. A focus on modifiers, that have not been considered yet for flotation of both lepidolite and zinnwaldite from silicates, is done. The objectives regarding Li-micas beneficiation including, selective flotation of micas from other silicates, such as quartz, albite and K-feldspar, production of marketable by-products, flotation of coarse and fine particles are critically analysed. Finally, the possible separation between micas is discussed with both crystallography and surface features and microflotation tests. Achieving such a separation would make it possible to increase the selectivity between lithium bearing micas and usual micas that could be present in ore deposits.